Dynamic Conservation in Risk Society: A Case Study of COVID-19 Pandemic Risk in Kashan Qanat Irrigated Agriculture - Manian, Mohammad ali; Khoshbakht, Korous; Mahmoudi, Hossein; Liaghati, Houman (Frontiers in Public Health, 2022)
In the present age, the world agricultural heritage can inspire agroecology and sustainable agriculture. But various risks have threatened, eroded and forgotten this heritage, so dynamic conservation of this heritage is essential. In this study, “Qanat Irrigated Agricultural Heritage Systems, Kashan, Iran” which has been registered worldwide in the face of corona pandemic risks has been selected as a case study. In this qualitative research, in addition to field observations and documentary studies, 25 in-depth interviews and 39 semi-structured interviews with experts and key informants was done and grounded theory and content analysis have been used. In the process of interviews and analyzes based on “risk society theory”, risks and wicked problems and related solutions have been identified and finally based on cultural theory, “clumsy solution space” has been summarized and presented for dynamic conservation. Based on the findings of this study, paying attention to a kind of reward for ecosystem services, developing online sales of agricultural products in rural areas of Kashan and also creating twinning with similar areas can help solve wicked problems. Also, paying more attention to the regulations for the protection of qanats, as well as the laws for home business insurance, can strengthen sustainable development in this rural area. Due to the wide range of different dimensions of agricultural heritage, it is suggested that in future research, clumsy solution spaces for each of these dimensions be created and developed separately.